The Relationship between Science Teacher Candidates’ Attitudes towards Teaching Profession and Their Self-Efficacy Beliefs towards Teaching Science - Sibel Açışlı Çelik; İsmet Ergin (Dinamika Ilmu, 2022)
This study was aimed to examine the relationship between pre-service science teachers' attitudes toward the teaching profession, their learning styles, and their self-efficacy beliefs toward teaching science. The sample of the research consisted of 127 teacher candidates studying in the Science Education Department of a state university in the 2020-2021 academic year. The data collection tool in the research was the Science Teaching Self-Efficacy Belief Scale; Kolb Learning Style Inventory III and Attitude towards Teaching Profession Scale were used. The research model is the relational survey model, which is under the general survey model. In the survey method, the aim is to uncover a statement in detail. The analysis of the data was carried out with the SPSS statistical program. In the study, it was determined that pre-service science teachers generally have an assimilating learning style, and their learning styles differ according to their grade levels but not according to their gender. In the study, it was determined that teacher candidates generally have a positive attitude toward the teaching profession and their attitudes differ according to their grade levels but not according to their gender. In the study, it was determined that teacher candidates generally have a positive attitude towards the teaching profession and their attitudes differ according to their grade levels but not according to their gender. In addition, the pre-service science teachers' self-efficacy beliefs in science teaching were at a "sufficient" level; significant differences were found in the sub-dimensions of science self-efficacy, belief in efficacy, and outcome expectation, according to gender and grade levels. In addition, a significant relationship was found between pre-service teachers' attitudes toward the teaching profession and their learning styles. There is a positive but low-level relationship between pre-service teachers' level of result expectation, which is the science self-efficacy sub-dimension, and their attitudes towards the teaching profession; No significant relationship was found between the level of efficacy belief, which is the sub-dimension of science self-efficacy, and the attitude towards the teaching profession.